Republic of Poland : Arrangement Under the Flexible Credit Line; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Poland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper focuses on an arrangement under the Flexible Credit Line (FCL) for the Republic of Poland. Poland's macroeconomic performance has been very strong. The authorities believe that access under an FCL arrangement in the amount of SDR 13.69 billion could help maintain market access and safeguard against downside risks during the current period of high volatility and retrenchment in international capital markets. IMF staff concurs and believes that, given Poland's regional importance, the FCL may provide insurance not only to Poland, but also to the region more broadly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet